Testing the Moderating Effect of Resilience on the Relationship between Irrational Beliefs and Perceived Performance: Focusing on Ice Hockey Players - Ji-hyun Cho (Korean Association of Rational Emotive and Cognitive Behavior Therapy, 2026)
This study aimed to examine the relationship between irrational beliefs and perceived performance in ice hockey players, as well as to verify the moderating effect of resilience on this relationship. For this purpose, 183 ice hockey players affiliated with high schools and universities located in Seoul, registered with the KIHA in 2021, were selected as participants using a purposeful sampling method. The measurement tools utilized included the iPBI-2, K-CD-RISC-10, and a Perceived Performance Scale. Data were analyzed to conduct frequency analysis, CFA, reliability analysis, correlation analysis, hierarchical regression analysis, and moderation analysis via bootstrapping (n=5,000). The results were as follows. First, resilience showed a statistically significant positive correlation with perceived performance(r=.58, p